An Experimental Study of Coal Gangue Pulverization for Slurry Making and a Field Test on Hulusu Coal Mine Overburden Grouting - Jian Li; Dayang Xuan; Jialin Xu; Jianchao Xu (Applied Sciences)
Coal gangue is a solid waste produced in the coal mining process. During the mining process, mining-induced overburden fractures are a favorable place for the storage of coal gangue; therefore, coal gangue can be incorporated into filling materials for harmless disposal. Overburden isolated grout filling is a better technology for solid waste reduction, which is currently in development. This paper delves into the methodology of large-scale coal gangue disposal, utilizing this specific technology. With reference to fly ash granules and their slurry characteristics that have been previously applied successfully, raw gangue was pulverized and transformed into a slurry. This experiment then investigated the fundamental characteristics of the gangue powder solids and slurry. This study’s findings reveal that the composition types of granule oxides following gangue pulverization closely resemble those of fly ash, with minimal content differences observed between identical oxides. Regarding slurry characteristics, the plastic viscosity of fly ash slurry ranged from 0.45 to 145.2 mPa·s, whereas the plastic viscosity of gangue slurry varied between 2.1 and 56.4 mPa·s. Notably, the stability and fluidity of the gangue slurry surpassed those of the fly ash slurry. Furthermore, regarding the filling efficiency, the compaction coefficient of gangue slurry is less than that of fly ash. Consequently, under identical grouting conditions, a larger mass of solids can be disposed of using gangue slurry compared to fly ash. The research findings facilitate the implementation of a practice involving the overburden isolated grout filling of over million tons of coal gangue in the 21404 working face of the Hulusu coal mine, located in Inner Mongolia, China. This practice has demonstrated a daily filling capacity of up to 4000 t, accumulating to a total gangue filling mass of 1,068,000 t. This study’s findings present a viable and efficient approach to the large-scale, environmentally friendly disposal of coal gangue.